Factors Related to the Length of Stay for Patients With Schizophrenia: A Retrospective Study - Cheng, Peng; Wang, Lirong; Xu, Lizhi; Zhou, Ying; Zhang, Li; Li, Weihui (Frontiers in Psychiatry, 2022)
Background The length of stay (LOS) of patients with schizophrenia has been a wide concern of researchers. Reasonable management of the LOS to achieve a balance between quality of treatment and efficient medical source allocation has become a significant issue in clinical work in psychiatry. Figuring out the factors related to the LOS of schizophrenia patients can help optimize its management by the hospital. Method The essential information of patients was obtained from the electronic medical record system. The variables were divided into the following kinds: demographic, clinical, and biochemical. Univariate analysis and multivariate analysis were conducted to find the potential factors related to the LOS of schizophrenia patients. Receiver operating characteristic analyses were conducted to evaluate the accuracy of judging the LOS of the regression model. Result A total of 1,160 patients with schizophrenia were enrolled in our research. Our results demonstrated that the status of unmarried (single, separated, divorced, or widowed) and the abnormality of thyroid-stimulating hormone (TSH) were risk factors for the longer LOS of schizophrenia patients. The area under the curve was 0.576, which meant that the regression model had a certain predictive value. Conclusion To our knowledge, this research is the first study to analyze the effect of various factors, including the biochemical index, on the LOS of a single type of mental disorder. Marital status and TSH were proven to be related to the LOS of schizophrenia patients. The results of this study provided reference factors of LOS for clinical psychiatry, which will be helpful to the management of hospitalization and in optimizing the allocation of medical sources.